2002
DOI: 10.1007/s00439-002-0872-6
|View full text |Cite
|
Sign up to set email alerts
|

FMR1 haplotype analyses among Indians: a weak founder effect and other findings

Abstract: This study on allelic/haplotypic fragile X associations evaluated using STR (DXS548, FRAXAC1, FRAXAC2) and SNP (ATL1) markers flanking the (CGG) n locus of FMR1 is the first report from the large ethnically complex Indian population. Results have been compared with allele/haplotype distributions reported for other major ethnic groups, including White Caucasians, Africans, and Pacific Asians. Though overall allele frequency distributions at the individual loci are more similar to Western Caucasians compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…In the FRAXAC2 locus, six alleles were identified by us namely, 151, 152, 153, 154, 155, and 156. Studies on the English [Macpherson et al, 1994], Finns [Zhong et al, 1994], African‐Americans [Crawford et al, 2000], population from Greece and Cyprus [Syrrou et al, 1996], and the northern population of India [Sharma et al, 2003] showed the most frequent allele to be 153 (4+), which is also the most frequent allele in our population represented in 42% of the normal population. The 154 (4) allele was found to be the most frequent allele in fragile X samples in this study and the North Indian study.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In the FRAXAC2 locus, six alleles were identified by us namely, 151, 152, 153, 154, 155, and 156. Studies on the English [Macpherson et al, 1994], Finns [Zhong et al, 1994], African‐Americans [Crawford et al, 2000], population from Greece and Cyprus [Syrrou et al, 1996], and the northern population of India [Sharma et al, 2003] showed the most frequent allele to be 153 (4+), which is also the most frequent allele in our population represented in 42% of the normal population. The 154 (4) allele was found to be the most frequent allele in fragile X samples in this study and the North Indian study.…”
Section: Discussionmentioning
confidence: 56%
“…The heterozygosity of the control population (63.3%) studied by us is higher in comparison to the Chinese (33%), Thai (16.5%), and Caucasians (44%), which reflects the heterogeneity of the studied population. A study on an Indian population from the northern part of India [Sharma et al, 2003] also reveals a lower prevalence of the 194 allele, a situation similar to that observed among the populations of Cameroon and blacks in USA [Chiurazzi et al, 1996b and Crawford et al, 2000]. The modal allele 194 (46.6%) was found to be flanked by 192 at a frequency of 22.6% [Sharma et al, 2003].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In addition to loss of AGG interruptions, studies of normal and fragile X chromosomes in various populations have indicated that a substantial proportion of fragile X chromosomes are in linkage disequilibrium (LD) with a small subset of flanking DXS548‐FRAXAC1‐FRAXAC2 microsatellite marker haplotypes (Bonaventure et al 1998; Eichler et al 1996; Larsen et al 2000; Patsalis et al 1999; Pekarik et al 1999; Poon et al 1999; Sharma et al 2003; Zhong et al 1994). Eichler et al (1996) identified two pathways leading to a full mutation at different mutational rates and occurring on different fragile X haplotypes.…”
Section: Introductionmentioning
confidence: 99%